Mechanical Properties and Compression Performance of 3D Printed HIPS Polymer Lattice Structure - Jin, Feng; Lu, Wanqing; An, Xu; Zhu, Haifeng; Wang, Jun (Manufacturing Technology Journal, 2024)
With the development of 3D technology, more and more materials are being used for manufacturing and used in many fields, such as factory manufacturing, workshop manufacturing, food packaging, and even architectural design and civil engineering design. In particular, the mechanical properties of the 3D printed HIPS polymer unit cell structure are worthy of research and analysis, providing more valuable references for future material development. This study focused on the properties of HIPS polymer materials and the performance of HIPS polymer 3D printed lattice structures after Instron instrument compression testing. The experimental samples were divided into 4 groups and there were 4 different experimental variables for analysis and comparison. Finally, it was found through analysis that the HIPS polymer material has good compression resistance, and the structure is relatively stable. It can be used more in the fields of manufacturing, architectural design and civil engineering in the future.
Keywords: 3D print; HIPS polymer; Compression test; Lattice structure; Stress and strain relationship